Pancasila as a Legal Development Paradigm - Selvi Komalasari; Dea Amelia; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - Pancasila has experienced ups and downs in development, this is not caused by the weakness of the values contained in it, but rather leads to inconsistencies in its application. In line with the acceptance of the truth of the noble values of Pancasila, the current and enthusiasm for making Pancasila as a paradigm accelerated. History also records how from the past until now Pancasila has often been challenged which resulted in a crisis for the existence of the Indonesian nation. The challenges faced by Pancasila as the view of life and the basis of the state are always directly proportional to the challenges faced by the Unitary State of the Republic of Indonesia as a whole.